Painting Security System using TensorFlow Based Object Detection Method - PRASETYA, MUHAMMAD YOGA AKBAR; Anshori , M. Abdullah; Wijayanti , Rieke Adriati (Politeknik Negeri Malang, 2024)
Painting is an art form that should be preserved. Raden Saleh, Affandi, Hendra Gunawan, and Nyoman Gunarsa's paintings are among those of outstanding artistic worth. The existence of paintings may be jeopardized if the painting protection system is poor. Several well-known examples of art theft include the theft of Affandi's paintings in 1973 and Raden Saleh's paintings in 2007. Apart from famous paintings, personal paintings, which are equally expensive, are frequently stolen. This, of course, concerns the general public, particularly private art collectors with minimal security. Based on these problems, specific management is needed through the